Support room and playfulness: adaptation of games as a learning aid (Research, Society and Development, 2019)
The text discusses learning through playfulness with the use of the memory game adapted for the teaching of Portuguese and mathematics to the fourth and sixth years of elementary school attended in the Support Room. The authors who supported the research discuss games in the initial series, teacher training, and teacher practice. In the methodology, the authors discuss about qualitative research using the descriptive and experimental method. As a result, the students' significant improvement in learning in Portuguese and mathematics was noticed. Therefore, the studies pointed out that the students demonstrated assimilation in relation to the abilities and competences during the games. They also pointed out that the associations and relations of Portuguese and mathematics were being worked on in other curricular activities proposed by the teacher of the Support Room.